Chemoselective Preparation of Clickable Aryl Sulfonyl Fluoride Monomers: A Toolbox of Highly Functionalized Intermediates for Chemical Biology Probe Synthesis. (30th August 2016) - Fadeyi, Olugbeminiyi; Parikh, Mihir D.; Chen, Ming Z.; Kyne, Robert E.; Taylor, Alexandria P.; O'Doherty, Inish; Kaiser, Stephen E.; Barbas, Sabrina; Niessen, Sherry; Shi, Manli; Weinrich, Scott L.; Kath, John C.; et al.
Abstract: Sulfonyl fluoride (SF)‐based activity probes have become important tools in chemical biology. Herein, exploiting the relative chemical stability of SF to carry out a number of unprecedented SF‐sparing functional group manipulations, we report the chemoselective synthesis of a toolbox of highly functionalized aryl SF monomers that we used to quickly prepare SF chemical biology probes. In addition to SF, the monomers bear an embedded click handle (a terminal alkyne that can perform copper(I)‐mediated azide–alkyne cycloaddition). The monomers can be used either as fragments to prepare clickable SF analogues of drugs (biologically active compounds) bearing an aryl ring or, alternatively, attached to drugs as minimalist clickable aryl SF substituents. Abstract : Clickable chemical creations : A toolbox of trifunctional aryl sulfonyl fluoride (SF) monomers was created by expanding the scope of known synthetic transformations that can be carried out in the presence of SF. These monomers can be used as fragments to prepare clickable SF analogues of aryl ring‐containing drugs or attached to drugs as minimalist clickable aryl SF substituents.